2017
DOI: 10.1038/s41560-017-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-electrochemical production of compressed hydrogen from methane with near-zero energy loss

Abstract: Conventional production of hydrogen requires large industrial plants to minimise energy losses and capital costs associated with steam reforming, water-gas shift, product separation, and compression. Here we present a protonic membrane reformer (PMR) which produces high purity hydrogen from steam methane reforming in a single-stage process with near-zero energy loss. We use a BaZrO 3 -based proton-conducting electrolyte deposited as a dense film on a porous Ni composite electrode with dual function as a reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 34 publications
0
119
0
Order By: Relevance
“…Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive. Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive.…”
Section: Currentfabrication Methods Of Anode-supported Cells and Perspmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive. Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive.…”
Section: Currentfabrication Methods Of Anode-supported Cells and Perspmentioning
confidence: 99%
“…Currently,t he mostc ommons tructure for BZY20 electrolytebased cells is an anode-supported one, which is composed of at hick anode layer and at hin electrolyte layer,c oupled with a co-sintering process and an optionals intering additive, which allowst he implementation of electrolyte layers thinned to tens of micrometers with minimized loss of ohmic resistance. Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive. Al iterature review revealed that the co-sintered cells have a conductivity of approximately 0.001-0.003Scm À1 (Table1), in accordance with the resultsi nt his work;t hat is, the BZY20 sample dopedw ith 1o r2wt %N iO had ac onductivity (mainly proton conduction) lower than 0.004 Scm À1 in wet hydrogen (Figure 9).…”
Section: Currentfabrication Methods Of Anode-supported Cells and Perspmentioning
confidence: 99%
“…This is useful to model the thermal expansion of certain electrode materials, requiring high ionic and electronic conductivity. For instance, for mixed protonic-electronic conduction, a cermet consisting of Ni and BaCe 0.9−x Zr x Y 0.1 O 3−δ -providing electronic and protonic conductivity, respectively-can typically be used in a proton ceramic electrochemical cell [7,8,10]. These models can also be applied to polycrystalline single-phase materials composed of anisotropic grains with random crystal orientations and thermal expansion coefficients.…”
Section: Significance and Relation Between Bulk And Lattice Expansionmentioning
confidence: 99%
“…If electronic transport is comparable with (or higher than) the ionic one, electrode‐free membranes for hydrogen‐separation reactors and electrode materials for electrode‐based SOCs can be purposefully designed . Unconventional proton transport for oxide materials allows the unique processes to be also carried out, for example, a precise H/D/T‐isotope analysis, conversion of harmful (NO x ) or widely available compounds (CO 2 ) to harmless and valuable products (N 2 , CO), conversion of saturated hydrocarbon (CH 4 , C 2 H 6 ) to unsaturated or aromatic compounds (C 2 H 4 , C 6 H 6 ), hydrogen compression, etc …”
Section: Introductionmentioning
confidence: 99%